Assessing the spatiotemporal characteristics and driving factors of habitat quality in sustainable development demonstration zones: a case study of Guilin City, China - Xu, Jingfeng; Fan, Deqin; Wang, Fangzhen; Zhao, Xuesheng; Ma, Wentao; Duan, Jialing (Frontiers in Environmental Science, 2025)
Guilin City, located in a typical karst landform area in China, is one of the sustainable development demonstration zones. Evaluating the habitat quality of Guilin City and exploring its driving factors are helpful in formulating effective measures for sustainable development. Based on the Integrated Valuation of Ecosystem Servicesand Tradeoffs (InVEST) model and combined methods such as spatial autocorrelation analysis, Geographical detector model and Geographically weighted regression (GWR) model, this study evaluated the habitat quality of Guilin City from 2001 to 2022. The study also analyzed the spatiotemporal characteristics and their possible driving factors. The results indicate that: (1) The average habitat quality in Guilin City was 0.59, with 47.98% of the area classified as having good or excellent habitat quality; however, habitat quality has shown a downward trend over the past 22 years. (2) Moran’s I values for habitat quality in Guilin City were all greater than 0.8, indicating a significant positive spatial correlation and spatial clustering. Among these, the low–low aggregation regions were the largest, whereas the high–high aggregation regions showed the most significant decrease. (3) Elevation was the most significant factor affecting the spatial differentiation of habitat quality in Guilin. The interactions between various driving factors were stronger than those between any single factor, with most interactions exhibiting a dual-factor enhancement effect. This study highlights the complexity of the comprehensive impact of multiple factors on habitat quality changes and provides a scientific basis and policy recommendations for ecological protection within the national sustainable development agenda’s innovative demonstration zones.